CH3NH3PbI3 perovskite thin film, cell and preparation method of CH3NH3PbI3 perovskite thin film
The preparation of CH3NH3PbI3 films by intermolecular exchange method has solved the problems of poor crystallization performance and phase film defects of perovskite films, and significantly improved the conversion efficiency of solar cells.
Patent Information
- Application Number
- CN202311289977.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The crystallization performance of the existing CH3NH3PbI3 perovskite film is poor, and has phase film defects, which affects the conversion efficiency of solar cells.
The CH3NH3PbI3 film was prepared by intermolecular exchange method, and the mesophase film was prepared by one-step spin coating on an FTO/TiO2 substrate, and spin coating was used for IPA solution at room temperature to obtain high-quality CH3NH3PbI3 film.
It improves the crystallinity of the CH3NH3PbI3 film, effectively repairs phase film defects, and improves the conversion efficiency of solar cells.
Smart Images

Figure CN119730654A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar cells, and in particular relates to a CH3NH3PbI3 perovskite film, a battery and a preparation method thereof. Background Art
[0002] Thin-film solar cells with perovskite-type organic lead iodine compounds as light-absorbing materials are another new type of solar cells based on nano-TiO2 after dye sensitization and quantum dot sensitization. Perovskite organic lead iodine compounds (such as CH3NH3PbI3) have unique photoelectric properties, and show excellent photoelectric conversion efficiency in liquid sensitized cells and solid-state thin-film cells based on hole transport materials. At the same time, perovskite crystal materials also have good electron and hole transport properties, which provides a basis for the preparation of perovskite-type planar heterojunction solar cells. Organic lead iodine compounds are self-assembled crystals with perovskite structures. Short-chain organic ions, lead ions, and halogen ions occupy the A, B, and X positions of the perovskite lattice, respectively, thus forming a three-dimensional structure. The long-chain ordered PbI3-octahedron system is conducive to the transmission of electrons, making this type of material have very excellent electron transport properties. Perovskite organic lead iodine compounds have a suitable energy band structure and good light absorption properties. They can absorb almost all visible light for photoelectric conversion. At the same time, this type of material has the characteristics of self-assembly, so it is easy to synthesize and effective thin film deposition can be achieved through a low-cost liquid phase method.
[0003] Conventional CH3NH3PbI3 perovskite film preparation is a thermal annealing method. After anhydrous ether is added to the surface of the precursor film, it is transferred to a hot stage with a preset temperature of 100 degrees Celsius. After heating for 10 minutes and naturally cooling to room temperature, a thermally annealed CH3NH3PbI3 film can be obtained. Since the solubility of PbI2 is lower than that of CH3NH3I, PbI2 precipitates earlier after anti-solvent immersion, resulting in poor crystallization performance of the prepared CH3NH3PbI3 film. At the same time, there are many inherent composition defects in the intermediate phase film, which ultimately affect the conversion efficiency of the perovskite battery.
[0004] Therefore, it is necessary to provide a method for preparing a perovskite film by intermolecular exchange, so that the perovskite film has better crystallinity, effectively repairs phase film defects, and improves the conversion efficiency of the prepared battery. Summary of the invention
[0005] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a CH3NH3PbI3 perovskite film and a preparation method thereof, and to prepare the perovskite film by an intermolecular exchange method, so that the perovskite film has better crystallinity, and effectively repairs phase film defects, thereby improving the conversion efficiency of the prepared battery.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a CH3NH3PbI3 perovskite film, comprising:
[0008] Cleaning FTO glass;
[0009] The cleaned FTO glass was used as substrate, and a dense TiO2 layer was prepared by a sol-gel method to obtain a FTO / TiO2 substrate.
[0010] The CH3NH3PbI3 mesophase thin film was prepared on the surface of FTO / TiO2 substrate by one-step spin coating method;
[0011] The IPA solution was spin-coated on the surface of the mesophase film at room temperature to obtain a CH3NH3PbI3 film;
[0012] The IPA solution includes CH3NH3I with a concentration of 2.8-3.2 mg / mL and CH3NH3Cl with a concentration of 1.8-2.2 mg / mL.
[0013] Further, cleaning the FTO glass includes:
[0014] Clean the FTO glass for the first time with an oil cleaner;
[0015] After the first cleaning, the FTO glass was ultrasonically cleaned with deionized water, acetone, and ethanol for 20 minutes in sequence;
[0016] The FTO glass after ultrasonic cleaning is cleaned with ultraviolet ozone for 25-35 minutes.
[0017] Furthermore, a TiO2 dense layer is prepared by a sol-gel method, comprising:
[0018] Preparing TiO2 sol;
[0019] Add 90-110 μl of TiO2 sol to the center of the FTO glass, and then spin at 2800-3200 rpm for 28-32 seconds;
[0020] The FTO glass after the spin coating is annealed in an air atmosphere at 470-490° C. for 55-65 minutes, and then air-cooled to room temperature to obtain a FTO / TiO2 substrate.
[0021] Further, the TiO2 sol is prepared, comprising:
[0022] Add 4-6 ml of tetrabutyl titanate solution dropwise into 30-40 ml of anhydrous ethanol and stir for 50-70 minutes to obtain a tetrabutyl titanate / ethanol solution;
[0023] Add 1.2-2.5 ml of diethanolamine solution dropwise into 7-8 ml of anhydrous ethanol, stir for 8-12 minutes, and then add 0.8-1.2 ml of deionized water dropwise to obtain a mixed solution;
[0024] Under stirring, the mixed solution was added dropwise into the tetrabutyl titanate / ethanol solution, and stirring was continued for 50-70 minutes and allowed to stand for 3 days to obtain a TiO2 sol without precipitation.
[0025] Further, a CH3NH3PbI3 mesophase thin film is prepared on the surface of the FTO / TiO2 substrate by a one-step spin coating method, comprising:
[0026] Prepare CH3NH3PbI3 precursor solution;
[0027] The precursor solution was added dropwise to the center of the FTO / TiO2 substrate and spin-coated at 5000 rpm for 23-27 s;
[0028] After spin coating at 5000 rpm for 5-7 s, 490-510 μL of anhydrous ether was continuously added to the center of the FTO / TiO2 substrate.
[0029] Further, a CH3NH3PbI3 precursor solution is prepared, including:
[0030] Add 458-463 mg of PbI2, 157-161 mg of CH3NH3I and 72-76 μL of DMSO to 590-610 mL of DMF and mix and stir to obtain a CH3NH3PbI3 precursor solution.
[0031] Further, the IPA solution is spin-coated on the surface of the mesophase film at room temperature, comprising:
[0032] 0.3-0.7 mL of IPA solution was spin-coated on the surface of the mesophase film.
[0033] Furthermore, the CH3NH3PbI3 film is dark brown.
[0034] In a second aspect, the present invention discloses a CH3NH3PbI3 perovskite film, which is prepared by the above method.
[0035] In a third aspect, the present invention discloses a perovskite battery, which is made of the above-mentioned CH3NH3PbI3 perovskite film.
[0036] Technical effects and advantages of the present invention:
[0037] The present invention prepares a CH3NH3PbI3 thin film by using an intermolecular exchange method, so that the CH3NH3PbI3 thin film has better crystallinity, effectively repairs phase film defects, and improves the conversion efficiency of the prepared battery.
[0038] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a flow chart of a method for preparing a CH3NH3PbI3 perovskite film according to the present invention;
[0040] Figure 2 XRD patterns of the CH3NH3PbI3 intermediate phase thin films of Example 2 and the comparative example of the present invention and the CH3NH3PbI3 thin films prepared by two methods;
[0041] Figure 3 FTIR measurement graphs of the CH3NH3PbI3 intermediate phase thin film of Example 2 of the present invention and the comparative example and the CH3NH3PbI3 thin films prepared by two methods;
[0042] Figure 4 The XPS graphs of Pb 4f and I 3d of the CH3NH3PbI3 thin films prepared in Example 2 of the present invention and the comparative example;
[0043] Figure 5 The Cl 2p XPS graphs of the CH3NH3PbI3 thin films prepared in Example 2 of the present invention and the comparative example. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] like Figure 1 As shown, the present invention provides a method for preparing a CH3NH3PbI3 perovskite film, comprising:
[0046] Cleaning FTO glass;
[0047] The cleaned FTO glass was used as substrate, and a dense TiO2 layer was prepared by a sol-gel method to obtain a FTO / TiO2 substrate.
[0048] The CH3NH3PbI3 mesophase thin film was prepared on the surface of FTO / TiO2 substrate by one-step spin coating method;
[0049] The IPA solution was spin-coated on the surface of the mesophase film at room temperature to obtain a CH3NH3PbI3 film;
[0050] The IPA solution includes CH3NH3I with a concentration of 2.8-3.2 mg / mL and CH3NH3Cl with a concentration of 1.8-2.2 mg / mL.
[0051] In some embodiments of the present invention, cleaning FTO glass includes:
[0052] Clean the FTO glass for the first time with an oil cleaner;
[0053] The FTO glass after the first cleaning was ultrasonically cleaned with deionized water, acetone and ethanol for 20 minutes in sequence;
[0054] The FTO glass after ultrasonic cleaning is treated with ultraviolet ozone cleaning for 25-35 minutes to improve the surface wettability of the FTO glass.
[0055] In some embodiments of the present invention, a TiO2 dense layer is prepared by a sol-gel method, comprising:
[0056] Preparing TiO2 sol;
[0057] Add 90-110 μl of TiO2 sol to the center of the FTO glass, and then spin at 2800-3200 rpm for 28-32 seconds;
[0058] The FTO glass after the spin coating is annealed in an air atmosphere at 470-490° C. for 55-65 minutes, and then air-cooled to room temperature to obtain a FTO / TiO2 substrate.
[0059] In some embodiments of the present invention, the TiO2 sol is prepared, comprising:
[0060] Add 4-6 ml of tetrabutyl titanate solution dropwise into 30-40 ml of anhydrous ethanol and stir for 50-70 minutes to obtain a tetrabutyl titanate / ethanol solution;
[0061] Add 1.2-2.5 ml of diethanolamine solution dropwise into 7-8 ml of anhydrous ethanol, stir for 8-12 minutes, and then add 0.8-1.2 ml of deionized water dropwise to obtain a mixed solution;
[0062] Under stirring, the mixed solution was added dropwise into the tetrabutyl titanate / ethanol solution, and stirring was continued for 50-70 minutes and allowed to stand for 3 days to obtain a TiO2 sol without precipitation.
[0063] In some embodiments of the present invention, a CH3NH3PbI3 mesophase thin film is prepared on a FTO / TiO2 substrate surface by a one-step spin coating method, comprising:
[0064] Prepare CH3NH3PbI3 precursor solution;
[0065] The precursor solution was added dropwise to the center of the FTO / TiO2 substrate and spin-coated at 5000 rpm for 23-27 s;
[0066] After spin coating at 5000 rpm for 5-7 s, 490-510 μL of anhydrous ether was continuously added to the center of the FTO / TiO2 substrate.
[0067] In some embodiments of the present invention, a CH3NH3PbI3 precursor solution is prepared, comprising:
[0068] Add 458-463 mg of PbI2, 157-161 mg of CH3NH3I and 72-76 μL of DMSO to 590-610 mL of DMF and mix and stir to obtain a CH3NH3PbI3 precursor solution.
[0069] In some embodiments of the present invention, spin coating the IPA solution on the surface of the mesophase film at room temperature comprises:
[0070] 0.3-0.7 mL of IPA solution was spin-coated on the surface of the mesophase film.
[0071] In some embodiments of the present invention, the CH3NH3PbI3 film is dark brown.
[0072] In a second aspect, the present invention discloses a CH3NH3PbI3 perovskite film, which is prepared by the above method.
[0073] In a third aspect, the present invention discloses a perovskite battery, which is prepared using the above-mentioned CH3NH3PbI3 perovskite film.
[0074] In order to better illustrate the present invention, the following examples and comparative examples are provided.
[0075] Example 1
[0076] Step 1: First, use an oil cleaner (deionized water, isopropanol, acetone, ethanol) to clean the surface oil of the FTO glass until there is no obvious water column left when rinsing with running water. Then, use deionized water, acetone, and ethanol to ultrasonically clean for 20 minutes in sequence, blow dry with high-purity nitrogen, and finally use ultraviolet ozone cleaning for 25 minutes to improve the surface wettability of the FTO glass.
[0077] Step 2: Measure 4 ml of tetrabutyl titanate solution, add it dropwise into 30 ml of anhydrous ethanol, and stir continuously for 50 minutes to obtain a tetrabutyl titanate / ethanol solution;
[0078] 1.2 ml of diethanolamine solution was added dropwise to 7 ml of anhydrous ethanol, and after being stirred for 8 minutes, 0.8 ml of deionized water was added dropwise to obtain a mixed solution;
[0079] Under continuous stirring, the mixed solution was added dropwise into the tetrabutyl titanate / ethanol solution, and the stirring was continued for 50 minutes, and then the mixture was allowed to stand for 3 days to observe if there was no obvious precipitation, thus obtaining the TiO2 sol.
[0080] The cleaned FTO glass was used as the substrate, 90 microliters of TiO2 sol was dripped at the center of the substrate, and then the substrate was spun at 2800 rpm for 28 seconds and then placed in a muffle furnace. After annealing at 470°C in an air atmosphere for 55 minutes, the substrate was naturally cooled to room temperature to obtain a FTO / TiO2 substrate.
[0081] Step 3: Add 458 mg of PbI2, 157 mg of CH3NH3I and 72 μL of DMSO into 590 mL of DMF and mix to obtain a CH3NH3PbI3 precursor solution;
[0082] 45 μL of pre-prepared CH3NH3PbI3 precursor solution was measured and dropped to the center of the FTO / TiO2 substrate, and then spin-coated at 5000 rpm for 23 seconds. After 5 seconds of the spin-coating process, 490 μL of anhydrous ether was continuously dropped to the center of the FTO / TiO2 substrate to obtain a CH3NH3PbI3 intermediate phase film.
[0083] Step 4: Spin coat 0.3 mL of IPA solution (containing 2.8 mg / mL CH3NH3I and 1.8 mg / mL CH3NH3Cl) on the intermediate phase film. It can be found that the color of the intermediate phase film quickly turns dark brown. After the spin coating process is completed, a room temperature crystallized CH3NH3PbI3 film can be obtained.
[0084] The conversion efficiency of the battery prepared by the prepared CH3NH3PbI3 thin film was detected to be 18.65%.
[0085] Example 2
[0086] Step 1: First, use an oil cleaner (deionized water, isopropanol, acetone, ethanol) to clean the oil on the surface of the FTO glass until there is no obvious water column left when rinsing with running water. Then, use deionized water, acetone, and ethanol to ultrasonically clean for 20 minutes in sequence, blow dry with high-purity nitrogen, and finally use ultraviolet ozone cleaning for 35 minutes to improve the surface wettability of the FTO glass.
[0087] Step 2: Measure 6 ml of tetrabutyl titanate solution, add it dropwise into 40 ml of anhydrous ethanol, and stir continuously for 70 minutes to obtain a tetrabutyl titanate / ethanol solution;
[0088] 2.5 ml of diethanolamine solution was added dropwise to 8 ml of anhydrous ethanol, and after being stirred for 12 minutes, 1.2 ml of deionized water was added dropwise to obtain a mixed solution;
[0089] Under continuous stirring, the mixed solution was added dropwise into the tetrabutyl titanate / ethanol solution, and the stirring was continued for 70 minutes, and then the mixture was allowed to stand for 3 days to observe that no obvious precipitation was found, and TiO2 sol was obtained;
[0090] The cleaned FTO glass was used as the substrate, 110 μl of TiO2 sol was dripped at the center of the substrate, and then the substrate was spun at 3200 rpm for 32 seconds and then placed in a muffle furnace. After annealing at 490°C in an air atmosphere for 65 minutes, the substrate was naturally cooled to room temperature to obtain a FTO / TiO2 substrate.
[0091] Step 3: Add 463 mg of PbI2, 161 mg of CH3NH3I and 76 μL of DMSO into 610 mL of DMF and mix to obtain a CH3NH3PbI3 precursor solution;
[0092] 50 μL of pre-prepared CH3NH3PbI3 precursor solution was measured and dropped to the center of the FTO / TiO2 substrate, and then spin-coated at 5000 rpm for 27 seconds. 7 seconds after the start of the spin-coating process, 510 μL of anhydrous ether was continuously dropped to the center of the FTO / TiO2 substrate to obtain a CH3NH3PbI3 intermediate phase film;
[0093] Step 4: Spin coat 0.7 mL of IPA solution (containing 3.2 mg / mL CH3NH3I and 2.2 mg / mL CH3NH3Cl) on the intermediate phase film. It can be found that the color of the intermediate phase film quickly turns dark brown. After the spin coating process is completed, a room temperature crystallized CH3NH3PbI3 film can be obtained.
[0094] The conversion efficiency of the battery prepared by the prepared CH3NH3PbI3 thin film was detected to be 18.67%.
[0095] Comparative Example
[0096] Step 1: First, use an oil cleaner (deionized water, isopropanol, acetone, ethanol) to clean the oil on the surface of the FTO glass until there is no obvious water column left when rinsing with running water. Then, use deionized water, acetone, and ethanol to ultrasonically clean for 20 minutes in sequence, blow dry with high-purity nitrogen, and finally use ultraviolet ozone cleaning for 35 minutes to improve the surface wettability of the FTO glass.
[0097] Step 2: Measure 6 ml of tetrabutyl titanate solution, add it dropwise into 40 ml of anhydrous ethanol, and stir continuously for 70 minutes to obtain a tetrabutyl titanate / ethanol solution;
[0098] 2.5 ml of diethanolamine solution was added dropwise to 8 ml of anhydrous ethanol, and after being stirred for 12 minutes, 1.2 ml of deionized water was added dropwise to obtain a mixed solution;
[0099] Under continuous stirring, the mixed solution was added dropwise into the tetrabutyl titanate / ethanol solution, and the stirring was continued for 70 minutes, and then the mixture was allowed to stand for 3 days to observe that no obvious precipitation was found, and TiO2 sol was obtained;
[0100] The cleaned FTO glass was used as the substrate, 110 μl of TiO2 sol was dripped at the center of the substrate, and then the substrate was spun at 3200 rpm for 32 seconds and then placed in a muffle furnace. After annealing at 490°C in an air atmosphere for 65 minutes, the substrate was naturally cooled to room temperature to obtain a FTO / TiO2 substrate.
[0101] Step 3: Add 463 mg of PbI2, 161 mg of CH3NH3I and 76 μL of DMSO into 610 mL of DMF and mix to obtain a CH3NH3PbI3 precursor solution;
[0102] 50 μL of pre-prepared CH3NH3PbI3 precursor solution was measured and dropped to the center of the FTO / TiO2 substrate, and then spin-coated at 5000 rpm for 27 seconds. 7 seconds after the start of the spin-coating process, 510 μL of anhydrous ether was continuously dropped to the center of the FTO / TiO2 substrate to obtain a CH3NH3PbI3 intermediate phase film;
[0103] Step 4:
[0104] The CH3NH3PbI3 intermediate phase film is transferred to a hot stage with a preset temperature of 100 degrees Celsius. After heating for 10 minutes, it is naturally cooled to room temperature to obtain a thermally annealed CH3NH3PbI3 film.
[0105] The conversion efficiency of the battery prepared by the prepared CH3NH3PbI3 thin film was detected to be 15.21%.
[0106] Figure 2Figure 2 shows the XRD patterns of the CH3NH3PbI3 intermediate phase films of Example 2 and the comparative example and the CH3NH3PbI3 films prepared by the two methods. In the figure, the diffraction peaks of the intermediate phase composed of the CH3NH3I-PbI2-DMSO complex can be clearly observed, indicating that both thermal annealing and intermolecular exchange can effectively remove the DMSO molecules from the intermediate phase and convert it into pure CH3NH3PbI3. The above process can be inferred from the characteristic diffraction peaks of the film located at 14.0°, 28.3° and 31.8°, which correspond to the (110), (220) and (310) planes of the tetragonal CH3NH3PbI3.
[0107] The CH3NH3PbI3 mesophase thin films of Example 2 and the comparative example and the CH3NH3PbI3 thin films prepared by the two methods were measured by Fourier transform infrared (FTIR). Figure 3 As shown in the figure, the 1010 cm-1 corresponding to the DMSO molecule can be clearly observed from the curve of the intermediate phase film. -1 The S=O stretching band at the pore size of the film is not found after thermal annealing or intermolecular exchange, which is completely absent in the film. These results indicate that, like thermal annealing, the intermolecular exchange pathway can also completely remove the DMSO molecules in the mesophase, thereby promoting the formation of CH3NH3PbI3. However, compared with thermal annealing, the key advantage of the intermolecular exchange pathway is that the mesophase transformation occurs at room temperature. In addition, it is worth noting that the diffraction peak intensity of the CH3NH3PbI3 film obtained by intermolecular exchange is stronger than that of the CH3NH3PbI3 film obtained by thermal annealing, indicating that it has better crystallinity.
[0108] XPS was used to study the elemental composition of the CH3NH3PbI3 films synthesized in Example 2 and the comparative example. Clear signals of C, N, Pb and I were detected from both samples, indicating that their compositions were similar, but there were certain differences in the atomic concentrations of Pb and I. In order to distinguish the differences, the peak intensities of the I 3d 5 / 2XPS core-level spectra of the two CH3NH3PbI3 films were normalized. The results are shown in Figure 2. Figure 4As shown in the figure, the Pb 4f peak intensity of the CH3NH3PbI3 film obtained by intermolecular exchange is much lower than that of the CH3NH3PbI3 film obtained by thermal annealing, and the relative atomic ratio of I / Pb is 2.95. These results show that the CH3NH3PbI3 film obtained by intermolecular exchange has a lower iodine deficiency, that is, fewer composition defects. It is worth noting that the atomic ratio of I / Pb calculated from the XPS spectrum of the intermediate phase film is 2.56, that is, there are many inherent composition defects in the intermediate phase film, which is largely due to the lower solubility of PbI2 than CH3NH3I, resulting in the earlier precipitation of PbI2 after anti-solvent immersion. This defect can be effectively repaired by the method of intermolecular exchange.
[0109] At the same time, if Figure 5 As shown in the figure, the characteristic peak of Cl 2p was observed in the CH3NH3PbI3 film obtained by intermolecular exchange, and the concentration of Cl atoms relative to I atoms was about 2.3 mol%. It was inferred that the observed Cl atoms were mainly obtained by Cl- atoms entering CH3NH3PbI3 to replace I-. The Cl- in the CH3NH3PbI3 film synthesized by chlorine-containing precursor was detected by XPS. The results showed that there was almost no Cl- on the surface of the final film, which indicates that Cl- can easily escape from the film during the annealing process. Therefore, when the film is prepared at room temperature, the presence of a small amount of Cl- is reasonable, but the concentration of Cl atoms is low, so the film is still marked with CH3NH3PbI3, indicating that the molecular exchange method can effectively repair and reduce defects in the film and improve the crystallization performance.
[0110] In summary, the present invention prepares a CH3NH3PbI3 thin film by using an intermolecular exchange method, so that the CH3NH3PbI3 thin film has better crystallinity, effectively repairs phase film defects, and improves the conversion efficiency of the prepared battery.
[0111] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a CH3NH3PbI3 perovskite film, characterized in that: include: Cleaning FTO glass; The cleaned FTO glass was used as substrate, and a dense TiO2 layer was prepared by a sol-gel method to obtain a FTO / TiO2 substrate. The CH3NH3PbI3 mesophase thin film was prepared on the surface of FTO / TiO2 substrate by one-step spin coating method; Spin-coating the IPA solution on the surface of the mesophase film at room temperature to obtain a CH3NH3PbI3 film; Wherein, the IPA solution includes CH3NH3I with a concentration of 2.8-3.2 mg / mL and CH3NH3Cl with a concentration of 1.8-2.2 mg / mL.
2. The method for preparing a CH3NH3PbI3 perovskite film according to claim 1, characterized in that: The cleaning of FTO glass comprises: Cleaning the FTO glass for the first time with an oily cleaning agent; After the first cleaning, the FTO glass was ultrasonically cleaned with deionized water, acetone, and ethanol for 20 minutes in sequence; The FTO glass after ultrasonic cleaning is cleaned with ultraviolet ozone for 25-35 minutes.
3. The method for preparing a CH3NH3PbI3 perovskite film according to claim 1, characterized in that: The sol-gel method is used to prepare the TiO2 dense layer, comprising: Preparing TiO2 sol; Add 90-110 μl of the TiO2 sol dropwise to the center of the FTO glass, and then spin the sol at a speed of 2800-3200 revolutions per second for 28-32 seconds; The FTO glass after the spin coating is annealed in an air atmosphere at 470-490° C. for 55-65 minutes, and then air-cooled to room temperature to obtain a FTO / TiO2 substrate.
4. The method for preparing a CH3NH3PbI3 perovskite film according to claim 3, characterized in that: The method for preparing TiO2 sol comprises: Add 4-6 ml of tetrabutyl titanate solution dropwise into 30-40 ml of anhydrous ethanol and stir for 50-70 minutes to obtain a tetrabutyl titanate / ethanol solution; Add 1.2-2.5 ml of diethanolamine solution dropwise into 7-8 ml of anhydrous ethanol, stir for 8-12 minutes, and then add 0.8-1.2 ml of deionized water dropwise to obtain a mixed solution; Under stirring, the mixed solution is added dropwise into the tetrabutyl titanate / ethanol solution, and the stirring is continued for 50-70 minutes and allowed to stand for 3 days to obtain a TiO2 sol without precipitation.
5. The method for preparing a CH3NH3PbI3 perovskite film according to claim 1, characterized in that: The one-step spin coating method is used to prepare a CH3NH3PbI3 mesophase film on the surface of the FTO / TiO2 substrate. include: Prepare CH3NH3PbI3 precursor solution; The precursor solution was dropped onto the center of the FTO / TiO2 substrate and spin-coated at a speed of 5000 rpm for 23-27 seconds; After spin coating at a speed of 5000 rpm for 5-7 seconds, 490-510 μL of anhydrous ether was continuously added dropwise to the center of the FTO / TiO2 substrate.
6. The method for preparing a CH3NH3PbI3 perovskite film according to claim 5, characterized in that: The CH3NH3PbI3 precursor solution is prepared, comprising: Add 458-463 mg of PbI2, 157-161 mg of CH3NH3I and 72-76 μL of DMSO to 590-610 mL of DMF and mix and stir to obtain a CH3NH3PbI3 precursor solution.
7. The method for preparing a CH3NH3PbI3 perovskite film according to claim 1, characterized in that: The method of spin coating the IPA solution on the surface of the mesophase film at room temperature comprises: 0.3-0.7 mL of IPA solution was spin-coated on the surface of the mesophase film.
8. The method for preparing a CH3NH3PbI3 perovskite film according to claim 1, characterized in that: The CH3NH3PbI3 film is dark brown.
9. A CH3NH3PbI3 perovskite film, characterized in that: The method is prepared by the method described in any one of claims 1 to 8.
10. A perovskite battery, characterized in that: The battery is made of the CH3NH3PbI3 perovskite film described in claim 9.